Resource Utilization and Costs of Care prior to ART Initiation for Pediatric Patients in Zambia - Hari S. Iyer; Callie A. Scott; Deophine Lembela Bwalya; Gesine Meyer-Rath; Crispin Moyo; Carolyn Bolton Moore; Bruce A. Larson; Sydney Rosen (AIDS Research and Treatment)
Objective. We estimated time to initiation, outpatient resource use, and costs of outpatient care during the 6 months prior to ART initiation for HIV-infected pediatric patients in Zambia. Methods. We enrolled 1,102 children who initiated ART at <15 years of age between 2006 and 2011 at 5 study sites. Of these, 832 initiated ART ≤6 months after first presenting to care at the study sites. Data on time in care and resources utilized during the 6 months prior to ART initiation were extracted from patient medical records. Costs were estimated from the provider’s perspective and are reported in 2011 USD. Results. For the patients who initiated ART ≤6 months after presenting to care, median age at presentation to care was 3.9 years; median CD4 percentage was 13%. Median time to ART initiation was 26 days. Patients made, on average, 2.38 clinic visits prior to ART initiation and received 0.81 CD4 tests, 0.74 full blood count tests, and 0.49 blood chemistry tests. The mean cost of pre-ART care was $20 per patient. Conclusions. Zambian pediatric patients initiating ART ≤6 months after presenting to care do so quickly, utilize fewer resources than mandated by national guidelines, and accrue low costs.